Transplantation of mononuclear cord stem cells at the refractory stage of heart failure - A. Usenko; А. Gabrielyan; T. Domanskyy; A. Yakushev; V. Onishchenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
This work is based on analysis of heart failure (HF) natural history in 20 patients who underwent cord blood stem cell transplantation by intravenous rout. After this study we have registered a significant increase in exercise tolerance, improvement of life quality, reduction of heart failure signs and increase in the effectiveness of traditional schemes HF treatment.